The Relevance of Index Funds for Pension Investment in Equities - Shah, Ajay; Fernandes, Kshama (World Bank, Washington, DC, 2014)
The rise of index funds over the past 25 years has been a remarkable phenomenon. The traditional rationale for the success of index funds is market efficiency, net of transaction costs. The authors also focus on the role of agency conflicts between fund managers and investors, which are hard to resolve, given the low power of statistical tests of performance. Most of the empirical evidence about the superiority of index funds comes from the United States. The authors discuss issues associated with the application of index funds in developing countries, as well as policy issues in the financial sector that affect the enabling market infrastructure for index funds. They also apply these ideas to thinking about the relevance of index funds for pension investment. The equity premium provides powerful motivation for equity investment by pension funds. Index funds make it possible to sidestep the complexities of forming contracts and monitoring institutions to govern fund managers. In developing countries that seek to use index funds in pension investment, there are avenues through which policymakers can make index funds more viable. In many countries there are significant avenues for improving construction of the market index as well as market mechanisms used in the equity market.